Humans Chromosome 1 Fractal Periods Signature is Highly Correlated with Intelligence and Brain Evolution - PEREZ Jean-claude (Journal of Glycomics And Metabolism, 2017)
DUF1220 proteins regions show the largest Homo-Sapiens lineage-specific increase in copy number of any protein-coding region in the human genome and map principally to 1q21.1. DUF1220 deletions have been associated with microcephaly and macrocephaly, respectively. DUF1220 copy number has been linked to both brain size in humans and brain evolution among primates. Remarkably, dosage variations involving DUF1220 sequences have now been linked to human brain expansion, autism severity, total IQ, and cognitive and mathematical aptitude scores. We analyzed in chromosome 1q a total of 245 DUF1220 proteins. Finally the method is extended analysing the long 1q21 region from 7 other close primates like Neanderthal, great apes : chimp, gorilla, orangutan and monkeys : macaque, marmoset, vervet. This remarkable property is confirmed by comparing these primates to other mammals such as mice, rabbit, cow, dolphin and Elephant. We then show four classes of multi-periodic fractal structures for all 19 DUF1220 regions and 19 NBPF genes studied cases. The analysis of these spectra of fractal periods1 reveals a simple linear interdependence, hierarchization and unification between the numerical sequences of each of these 4 spectra and the sequences of Fibonacci and Lucas. Given the evidence of this numerical relationship, we suggest that this discovery may be one of the major causes of a cognitive development of man superior to that of the great primates. Finally the mathematical roots of this whole numbers resonance patterns is discussed.
Keywords: Brain evolution